Magnetocrystalline anisotropy of 3d-4f intermetallics: Breakdown of the linear theory. - COEY, JOHN MICHAEL DAVID (American Physical Society, 1994)
Applicability of linear theory to magnetic anisotropy of 3d-4f intermetallics is investigated with particular reference to Sm2Fe17N3. A general quantitative criterion for the breakdown of the linear theory is established, according to which the theory falls beyond a 20% accuracy limit for most permanent magnet materials. By rigorous numerical treatment of published experimental data on high-field magnetization of Sm2Fe17N3, the crystal-field parameters are determined to be A20 =-333Ka0-2,A40=0.84Ka0-4. The linear theory fails for Sm2Fe17N3 due to its disregard for both J-mixing, predominant at all temperatures, and the intramultiplet nonlinear effects, important at low temperatures. Nevertheless these effects can be largely compensated for by rescaling the crystal-field parameters within the framework of the linear theory, which then provides an accurate analytical description of anisotropic magnetic properties of Sm2Fe17N3 in the practically important range of temperatures, T K.
PUBLISHED
Keywords: Physics